Java for beginners : step-by-step hands-on guide to Java - Aggarwal, Manuj (Packt Publishing, 2018)
"We are a group of coders and programmers ourselves. So we understand the importance of learning by doing. This course is jam-packed with practical demos, homework assignments and a lot of live coding which will help you immensely in grasping these complex topics. We begin by downloading and installing a free programming editor also known as an integrated development environment (IDE). The IDE is called Eclipse and is pretty popular amongst Java programmers. Then we will go through some basic and foundational concepts of the Java programming language. Many of these concepts also apply to other programming languages. After these core concepts - we will put things into high gear and talk about control flow statements which can help you write dynamic programs. We will discuss object-oriented programming and its various pillars. We will introduce you to important OOP concepts like objects, classes, inheritance, interfaces, and packages. Each discussion will focus on how these concepts relate to the real world, while simultaneously providing an introduction to the syntax of the Java programming language. The added power of OO programming which Java provides gives programmers a huge edge over the relative simplicity of procedural programming. OOP concepts make it easier for programmers to relate the code to the real world objects we see around us. Generally speaking, learning OOP could be very simple and complex at the same time. We strive to explain these essential concepts with the help of simple real world scenarios and exercises."--Resource description page